The Great Mindshift How a New Economic Paradigm and Sustainability Transformations go Hand in Hand - Göpel, Maja (The Anthropocene: Politik-Economics-Society-Science,, 2016)
Sustainable development is the 21st Century's wicked problem. After 40 years into this agenda have reversed only few unsustainable trends we hear the call for aparadigm shift, transformation, radical change or system innovations in order to finally change course. But what does this actually mean? And how do we put it into practice? This book describes the path ahead. It combines system transformation research with political economy and change leadership insights when discussing the need for a great mindshift in how human wellbeing, economic prosperity and healthy ecosystems are understood if the Great Transformations ahead are to lead to more sustainability. It shows that history is made by purposefully acting humans and introducestransformative literacy as a key skill in leading the radical incremental change strategies that wicked problems require, illustrating their nature through mapping pioneering practices and their commonalities. Mankind's search for a new narrative outside the 'planet stupid' discourse of GDP growth is in full swing. Maja Göpel's book is a field guide to our unfolding future. A must-read for leaders who seek to make sense of what's going on and ensure their organisations stay relevant. Mark Drewell, former CEO, Globally Responsible Leadership Initiative, Senior Partner The Foresight Group Reimagining the economy, and its purpose in our lives, is one of the key challenges of this century. Maja Göpel draws on an array of emerging ideas to show that it is not just a challenge but an opportunity, and one that has already taken root in inspiring initiatives around the world. Kate Raworth, Founder of 'doughnut economics', Senior Visiting Research Associate University of Oxford We want sustainable development. That requires profound changes in the way we explain and manage our societies. Maja Göpel shows how to do that. She offers the analytical framework for transformative change. Brilliant! Ernst Ulrich von Weizsäcker, Co-President Club of Rome For those seeking to understand and engage with our turbulent global moment, The Great Mindshift serves as a primer for the perplexed and a manifesto for the disheartened. .... Gramsci's observation that "the old is dying and the new cannot be born" has never been truer, and in Göpel we have a wise midwife to assist us in giving birth to a healthy planetary civilization. Paul Raskin, President, Tellus Institute and Founder, Great Transition Initiative Dr. Maja Göpel is Head of the Berlin Office of the Wuppertal Institut.